Awareness of civil servants in maintaining public property: a study at jabatan perkhidmatan veterinary negeri Selangor / Muhammad Hafizuddin Zamir Hassan - Hassan, Muhammad Hafizuddin Zamir (2019)
Vandalism symptoms often occur in Malaysia which has caused a lot of loss to the government due to the cost of repairing the damage. The vandalism symptoms often occur among adolescents and some of those who are already working. This possible due to the lack of education related to manners of public property. It happens everywhere and the creative ones will spell with words that are shameful and can cause anger. The creative naughty hands will continue to 'work' regardless of who the owner of the 'public property' is being damaged. This research is to study about awareness of civil servants in maintaining public property. Firstly, the researcher investigates the level of knowledge and understanding of civil servants about maintaining public property. Secondly, the researcher want to know the perception of civil servants relate to the maintaining of public property. Thirdly, this research purpose to examine the relationship between knowledge, understanding and perception of civil servants with their awareness in maintaining public property. The analysis of this research involved 50 respondents; all of them are civil servants from Jabatan Perkhidmatan Veterinar Negeri Selangor. For the methods of analysis. Frequency Distribution, Descriptive Analysis, Reliability Test, Pearson Correlation Coefficient and Hypothesis Tested were adopted to analyze the results. The results show that majority of the respondents aware that public property should be well maintained. Lastly, this study also provides recommendation for few aspects base on the results of the finding and recommendations for future research who wish to pursue this study or have an interest in doing the same research.